Effects of corn source and increasing lysine content on growth performance in swine - C W Hastad; Michael D Tokach; Jim L Nelssen; Robert D Goodband; Joel M DeRouchey; Steven S Dritz (Kansas Agricultural Experiment Station Research Reports, 2005)
Three studies were conducted to evaluate the effect on growth performance when NutriDense (ND) corn is used in conjunction with increasing amounts of L-lysine, threonine, and methionine. NutriDense corn is a nutritionally enhanced product containing a stacked set of traits to provide greater nutrient density than is provided by conventional yellow dent corn (YD). In Experiment 1, a total of 320 pigs (initial 40.2 lb) were blocked by weight to one of eight dietary treatments. Pigs were fed corn-soybean meal diets with either YD or ND corn and with 3, 5, 7, or 9 lb of crystalline L-lysine per ton of complete feed. Rates of methionine and threonine to lysine were balanced across all dietary treatments by the addition of DL-methionine and L threonine. There were no corn-source × L-lysine amount interactions in this experiment. Increasing L-lysine decreased ADG (linear, P<0.01) and worsened F/G (linear, P<0.01; quadratic, P<0.10). There was no effect (P>0.23) of corn source on ADG, ADFI, or final weight, but pigs fed diets with ND corn had improved (P<0.05) feed efficiency. Experiments 2 and 3 were conducted at a commercial swine research facility in southwestern Minnesota. In Experiment 2, a total of 1,189 gilts (initially 87.7 lb) were used; in Experiment 3, a total of 1,136 gilts (initially 187.3 lb) were blocked by weight in a 28-d growth assay. In both experiments, there were six dietary treatments that included either YD or ND corn and increasing amounts of Llysine HCl (3, 6, and 9 lb/ton). In Experiment 2, there were no corn-source × L-lysine content interactions. Increasing dietary L-lysine HCl decreased ADG (linear, P<0.01) and worsened F/G (linear, P<0.01; quadratic, P<0.08). Feeding pigs diets with ND corn increased (P<0.07) ADG and improved (P<0.01) feed efficiency. In Experiment 3, there was a corn source × L-lysine content interaction (P<0.02) for ADG and F/G. This interaction occurred because there was a greater decrease in ADG for pigs fed diets with YD corn and increasing Llysine, compared with ADG of pigs fed diets with ND corn. No other interactions were observed (P>0.53). Increasing L-lysine decreased ADG (quadratic, P<0.01) and worsened F/G (quadratic, P<0.01). Feeding pigs diets with ND corn increased (P<0.01) ADG and improved (P<0.01) F/G, but had no effect on ADFI. The use of ND corn in swine diets will reduce the amount of threonine and methionine needed when high concentrations of crystalline L-lysine are used in corn-soybean meal diets. Also, because ND corn has 34% more tryptophan than typical YD corn does, higher concentrations of L-lysine, in conjunction with threonine and methionine, can be used before tryptophan becomes the dietary limiting amino acid. These studies indicate that the use of ND corn can reduce the need for threonine and methionine supplementation when supplementing with more than 0.15% Llysine HCl.; Swine Day, 2005, Kansas State University, Manhattan, KS, 2005
Keywords: Swine day; 2005; Summary Publication of Report of Progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 964; Kansas Agricultural Experiment Station contribution; no. 06-63-S; L-lysine; Pigs; Yellow dent corn; Swine